Pengembangan Perangkat Pembelajaran PPKn Berbasis Model Predict, Observe, Explain (POE) dalam Meningkatkan Keterampilan Berpikir Kritis dan Pemahaman Konsep Siswa Kelas V Sekolah Dasar - Dimas Aditya Nugroho; Mustaji -; Raden Roro Nanik Setyowati (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2021)
This research aims to describe the results of the validity, practicality of learning devices, and the effectiveness of the integrated learning tools of the POE model to help student understanding of concept and famililiarize students with critical thinking skills. This research isa research development that adapting using a 4-D development model and data collection techniques using observations, questionnaires, and test. The trial was conducted in the 2019/2020 school year with a total of 20 research subjects. The results of the research that have been done prove that the POE model based learning process can be applied because it has good validity with an average value above 3.6, while for the evaluation of practicability it can be said to be weel proven in the implementation of learning which has an average have value of 79,5%, and the effectiveness of the learning process can be agreed affective based on the learning achievement test related to understanding concept and critical thinking skills before only 45% of students who completed it and after participating in learning up to 100% of students who completed it resulted with a value of ≥75.